Registration and Execution of Fiduciary Guarantees for Objects Located Abroad - Sinta Wahyu; Miftakhul Jannah (Jurnal Justiciabelen, 2025)
Private International Law is a national rule of law and is generally intended to promote efficient solutions to problems that arise when instances involving different legal systems occur across borders. There is a straightforward rule of international civil law called lex rei sitae that governs fiduciary grants. This rule establishes the applicable law as being the law of the location of the item. Therefore the author is interested in trying to dig deeper into the problem of fiduciary guarantee disputes using statutory and philosophical approaches to normative legal study that is analytically descriptive in nature which aims to describe or provide an overview of the law. The definition of Article 11 of the Fiduciary Guarantee Law states that objects burdened with a fiduciary guarantee must be registered both inside and outside the territory of the Republic of Indonesia, and that registration must take place at the residence of the fiduciary giver. Member States must make cross-border travel easier have traditionally coordinated the legal effects of the trans-border movement itself through private international law rules that date back to the Middle Ages, those rules that have withstood all attempts at modernization in private international law. Whereas in other disciplines, balancing the interests of the parties is given more focus.